IMPROVING STUDENT LEARNING OUTCOMES OF GRADE V BY USING THE THINK PAIR SHARE COOPERATIVE LEARNING MODEL IN THEMATIC LEARNING AT SDN SUNGAI SALAI HILIR - Adrian, Yudha (Universitas Muhammadiyah Lamongan, 2024)
This study aims to determine the effectiveness of the Think Pair Share cooperative learning model in improving student learning outcomes in thematic learning, especially theme 8 subtheme 3. This classroom action research was conducted at SDN Sungai Hilir involving 26 grade V students and homeroom teachers. The results showed a significant increase in student learning outcomes after the implementation of the Think Pair Share model. Student involvement in the learning process also increased, as evidenced by the increase from cycle I to cycle II. Teachers also showed an increase in managing learning by implementing the Think Pair Share cooperative model, as seen from the changes in cycle I and cycle II.